Continuous De-emulsification of Crude Oil Using Packed Column Under Various Conditions - R. Rassoul, G. A. (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
This research dealt with desalting of East Baghdad crude oil using pellets of either anionic, PVC, quartz, PE, PP ornonionic at different temperature ranging from 30 to 80 °C, pH from 6 to 8, time from 2 to 20 minutes, volume percentwashing water from 5 to 25% and fluid velocity from 0.5 to 0.8 m/s under voltage from 2 to 6 kV and / or using additivessuch as alkyl benzene sulphonate or sodium stearate. The optimum conditions and materials were reported to removemost of water from East Baghdad wet crude oil.